Intellectual Capital in Polish Corporate Groups : Current Trends and Future Challenges - Aluchna, Maria; Mierzejewska, Beata (Kapitał intelektualny w polskich grupach kapitałowych : współczesne trendy i przyszłe wyzwania, 2010)
Corporate groups, their functioning, management systems and aspects of efficiency remain in the center of academic research and debate. Research on functioning patterns and performance of corporate groups attracted interest of both academics and practitioners also in Poland, particularly during privatization processes. The paper is based on research conducted on the sample of selected Polish corporate groups and concentrates on their functioning, paying major attention to the process of development of intellectual capital within their complex structure. The research delivers insights into the importance of intellectual capital as a tool for building competitive advantage in rising economy and the challenges of assessing and reporting intellectual capital in corporate groups.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 167-181
Keywords: intellectual capital; corporate groups